PENGARUH MODEL PEMBELAJARAN TEAMS GAME TOURNAMENT (TGT) BERBANTUAN MEDIA MATH BINGO TERHADAP KETERAMPILAN BERHITUNG PERKALIAN - Siti Muniroh; Yunita Sari (Cahaya Smart Nusantara, 2025)
This study aims to analyze the effect of the Teams Games Tournament (TGT) learning model assisted by Math Bingo media on the multiplication calculation skills of second-grade students at SD N Karangroto 04. The method used is an experimental approach with a pre-experimental design of One Group Pretest-Posttest. The results show that the implementation of the TGT model with Math Bingo media significantly improves students' multiplication calculation skills. The average pretest score of students was 21.7, while the average posttest score increased to 43.5. The Paired Sample T-Test showed a significance value of 0.000 (p < 0.05), indicating a significant positive effect of this learning model on students' calculation skills. This study concludes that the use of the TGT model and Math Bingo media is effective in enhancing students' multiplication calculation skills.